Optical transmission systems based in direct detection with modulation in phase and amplitude - Domingues, Guilherme de Almeida (2022)
The need for optical communication systems has been increasing given the advancements in 5G and other parallel technologies. Therefore, it is required to develop low-cost high capacity solutions, particularly for short-reach systems, such as interdatacenters links. Current coherent transceivers can fulfill the capacity requirements, but their extended hardware components list make its solutions complex, power-hungry, and expensive, making it an unappealing solution for short-reach applications. Notice that a standard coherent receiver requires: two 90º optical hybrids, four pairs of balanced photodetectors, a local oscillator, and two polarization beam splitters for dual polarization schemes. State of the art self-coherent transceivers have a capacity competitive to coherent, in a short-reach scenario, while only requiring a single photodetector at the receiver. By employing single sideband methods who explore the DC-Value self-coherent algorithm, it is possible to recover the lost phase data upon photodetection. In this work, the DC-Value method is numerically and experimentally studied with the intent of exploring its limitations where it is found that the IQ modulation and the carrier contribution factor limit its capabilities. In a first stage, a deep analysis of the self-coherent DC-Value algorithm is performed. Here, an experimental validation was conducted to understand its limitations in terms of electro-optic modulation and carrier contribution factor. After, an investigation of the impact of the non-linear IQ modulator transfer function in the DC-Value through numerical and experimental work was carried out. By employing extra digital signal processing techniques, the experimental results show that high modulation depth signals can get a 2 dB EVM gain. Finally, an analysis of the impact of the carrier contribution factor estimation in the performance of the DC-Value method was conducted. It was shown by using a moving average filter that its estimation error reduced from 1.7% to 0.4%, which resulted in an EVM gain of 2.6 dB.